Persistence mechanisms in Pseudomonas aeruginosa from cystic fibrosis patients undergoing ciprofloxacin therapy. - Diver, J M (1991)
The mechanisms of persistence to ciprofloxacin in nine sets of Pseudomonas aeruginosa strains isolated during ciprofloxacin therapy of chronic lung infections in cystic fibrosis patients were studied. Low to moderate levels of ciprofloxacin resistance developed in each case. Each set of pretherapy ciprofloxacin-susceptible, during-therapy ciprofloxacin-resistant, and posttherapy ciprofloxacin-susceptible isolates were shown to be genotypically related by using a radiolabeled epidemiological gene probe. All ciprofloxacin-resistant isolates were found to have altered susceptibilities to both nalidixic acid and various chemically unrelated antibiotics. Analysis of possible resistance mechanisms showed that the strains had altered outer membrane protein or lipopolysaccharide profiles. Complementation of possible DNA gyrase mutations with a plasmid-borne, wild-type Escherichia coli gyrA gene indicated that altered DNA gyrase was at least partly responsible for ciprofloxacin resistance in all strains tested. Attempts to generate ciprofloxacin-susceptible revertants in vitro showed that in some strains reversion was rapid in the absence of ciprofloxacin, while in other strains it was not possible to generate revertants. These data indicate that persistence of Pseudomonas aeruginosa to ciprofloxacin involves changes in DNA gyrase and is associated with pleiotropic changes in outer membrane proteins and lipopolysaccharide.